Do arbuscular mycorrhizal fungi stabilize litter‐derived carbon in soil?. (14th November 2015) - Verbruggen, Erik; Jansa, Jan; Hammer, Edith C.; Rillig, Matthias C.
Summary: Fine roots and mycorrhiza often represent the largest input of carbon (C) into soils and are therefore of primary relevance to the soil C balance. Arbuscular mycorrhizal (AM) fungi have previously been found to increase litter decomposition which may lead to reduced soil C stocks, but these studies have focused on immediate decomposition of relatively high amounts of high‐quality litter and may therefore not hold in many ecological settings over longer terms. Here, we assessed the effect of mycorrhizal fungi on the fate of C and nitrogen (N) contained within a realistic amount of highly 13 C‐/ 15 N‐labelled root litter in soil. This litter was either added fresh or after a 3‐month incubation period under field conditions to a hyphal in‐growth core where mycorrhizal abundance was either reduced or not through rotation. After 3 months of incubation with a plant under glasshouse conditions, the effect of turning cores on residual 13 C and 15 N inside the cores was measured, as well as 13 C incorporation in microbial signature fatty acids and 15 N incorporation of plants. Turning of cores increased the abundance of fungal decomposers and 13 C loss from cores, while 15 N content of cores and plants was unaffected. Despite the difference in disturbance that turning the cores could have caused, the results suggest that mycorrhizal fungi and field incubation of litter acted to additively increase the proportion of 13 C left in cores. Synthesis . Apart from stimulating litter decomposition as previously shown, mycorrhizas can also stabilize C during litter decomposition and this effect is persistent through time. Abstract : Apart from stimulating litter decomposition as previously shown, mycorrhizas can also stabilize C during litter decomposition and this effect is persistent through time.